Rebel magisters - Swendson, Shanna (NLA Digital, LLC, 2016)
In an alternative 1888 New York, seventeen-year-old Verity Newton and her magister employer, Lord Henry, must work together to pull off a diplomatic mission that pits them against factions of both magisters and Mechanics.